Organizational features of operational service of lines by criminal police units - S. A. Chyzh (Law and Safety)
The emergence of new organizational and legal forms of management has created the preconditions for the merger of criminal offenses in the economy with general crime, in connection with which law enforcement agencies are brought to the forefront of organizational and tactical tasks to prevent crime in all sectors of the economy. objects and territories. Based on this, at this stage of economic development, the role and importance of operational maintenance of criminal police lines of work is growing rapidly. The article considers the existing scientific approaches to the definition of “operational service”, which allowed to formulate the author's position on the definition of “operational service of criminal police units of work lines” as a balanced organizational and managerial model of criminal police units on a particular line of work, which means the following: 1) operative overlapping of objects of operative attention by representatives of the agency network; 2) conducting control and supervision proceedings for the purpose of control, monitoring, analysis, assessment and forecasting of the operational situation along the line of work; 3) search and recording of factual data on illegal activities of individuals and groups; 4) use the possibilities of criminal analysis in order to create a single security space in all spheres and sectors of the economy and ensure an effective system of operational and investigative counteraction to criminal offenses that encroach on the functioning of the state economy. It is proved that effective organization of operative service of concrete subject of economic activity is a precondition for ensuring timely prevention and detection of criminal illegalities of economic orientation, and optimization of this direction of work is possible by creation of operative positions at the expense of secret workers. economic knowledge. Based on the analysis of the practical activities of criminal police units, the author identified ways to optimize the organization of operational maintenance of criminal police units work lines, including: 1) daily monitoring and analysis of the operational situation along the line of work; 2) determination for each object (branch) of economy of the corresponding mode of operative service (intensity of supervision) which needs constant operative attention, in particular by their operative overlapping; 3) preparation and determination of the most effective operational-search, operational-technical and agency-operational measures aimed at obtaining primary operational-search information along the line of work.